Micro Wave Energy Farming on Slender Pile Structure - Husna, Faliha; Rahmawati, Shade; Armono, Haryo Dwito (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2022)
The development of renewable energy technology has mostly beenfocused on macro-sized farming models. Recent studies have explored the benefits of micro wave energy to support offshore sensor networks. This paper discusses the viability of micro ocean energy farming of wave energy on slender pile structure through piezoelectric converters. Case study was obtained using Tuban environmental data from the year 2004-2009. Significant wave height and period were used to generate wave forces on slender pile and converted to electrical energy using simple piezoelectric converter equations. The resulting wave force on a 0.03m thick piezoelectric plate generates voltage of 0.6 Volt.